Double-Sine-Wave Quadri-Pulse Theta Burst Stimulation of Precentral Motor Hand Representation Induces Bidirectional Changes in Corticomotor Excitability - Jung, Nikolai H.; Gleich, Bernhard; Gattinger, Norbert; Kalb, Anke; Fritsch, Julia; Asenbauer, Elisabeth; Siebner, Hartwig R.; Mall, Volker (Frontiers in Neurology, 2021)
Neuronal plasticity is considered to be the neurophysiological correlate of learning and memory and changes in corticospinal excitability play a key role in the normal development of the central nervous system as well as in developmental disorders. In a previous study, it was shown that quadri-pulse theta burst stimulation (qTBS) can induce bidirectional changes in corticospinal excitability (1). There, a quadruple burst consisted of four single-sine-wave (SSW) pulses with a duration of 160 μs and inter-pulse intervals of 1.5 ms to match I-wave periodicity (666 Hz). In the present study, the pulse shape was modified applying double-sine-waves (DSW) rather than SSW pulses, while keeping the pulse duration at 160 μs. In two separate sessions, we reversed the current direction of the DSW pulse, so that its second component elicited either a mainly posterior-to-anterior (DSW PA-qTBS) or anterior-to-posterior (DSW AP-qTBS) directed current in the precentral gyrus. The after-effects of DSW qTBS on corticospinal excitability were examined in healthy individuals (n = 10) with single SSW TMS pulses. For single-pulse SSW TMS, the second component produced the same preferential current direction as DSW qTBS but had a suprathreshold intensity, thus eliciting motor evoked potentials (PA-MEP or AP-MEP). Single-pulse SSW TMS revealed bidirectional changes in corticospinal excitability after DSW qTBS, which depended on the preferentially induced current direction. DSW PA-qTBS at 666 Hz caused a stable increase in PA-MEP, whereas AP-qTBS at 666 Hz induced a transient decrease in AP-MEP. The sign of excitability following DSW qTBS at I-wave periodicity was opposite to the bidirectional changes after SSW qTBS. The results show that the pulse configuration and induced current direction determine the plasticity-effects of ultra-high frequency SSW and DSW qTBS at I-wave periodicity. These findings may offer new opportunities for short non-invasive brain stimulation protocols that are especially suited for stimulation in children and patients with neurological or neurodevelopmental disorders.